Variables posture in the sagittal plane in children attitude with scoliosis and idiopathic scoliosis - Jacek Wilczyński; Katarzyna Grzanka; Alicja Śliwa; Żaneta Wypych (Journal of Education, Health and Sport, 2018)
The aim of the study was to analyze the sagittal spinal curvatures in children with scoliosis and idiopathic scoliosis attitude and norm. The shape of the spine was assessed using optoelectronic Diers formetric III 4D. The research was Carried out in the Posturology Laboratory at the Faculty of Medicine and Health Sciences, UJK in Kielce (Poland). The biggest differences in the absolute values ​​of the variables tested in girls and boys with a group of scoliosis, attitudes and scoliotic standard body length was observed for SP-VP (mm). Univariate analysis of variance showed significant differences in the measurement of intra-lordosis angle among both boys and girls. This means that only the angles of lordosis differed significantly between the groups scoliosis, attitudes and scoliotic standard. Both girls and boys lordosis angle of scoliosis in the group was significantly lower than in the attitudes scolitic group and with the standard. In children with scoliosis it occurred in the first place to shallow lumbar lordosis. The size of the physiological thoracic kyphosis and lumbar lordosis should be taken into account in the selection of methods of treatment of scoliosis. In the treatment of scoliosis, use patterns shoulders and the pelvis, to restore the normal range thoracic kyphosis and lumbar lordosis.